Research Capacity for Operationalization of the Malawi Agricultural Sector Wide Approach (ASWAp) - Mapila, Mariam A.T.J.; Yauney, Jason; Droppelmann, Klaus; Thangata, Paul Howard (International Food Policy Research Institute, 2012)
The Agricultural Sector-Wide Approach (ASWAp) aims to support priority activities in the agricultural sector in Malawi that would increase agricultural productivity, reduce hunger, enable people access to nutritious foods, and increase the contribution of agroprocessing to economic growth.i ASWAp directly supports the objective of the Malawi Growth and Development Strategy (MGDS) of reducing poverty and transforming the economy from an importing and consuming to a manufacturing and exporting one. Agricultural research plays a vital role in making the ASWAp programme a success; yet, to date there has been no effort to explicitly link the research strategies of the National Agricultural Research System (NARS) institutions to the ASWAp research agenda. Thus, as a first step toward facilitating the development of an “ASWAp-responsive” research strategy for NARS institutions, the International Food Policy Research Institute (IFPRI), under the auspices of its Malawi Strategy Support Program (MaSSP), conducted an assessment of the strategic research and planning capacity within NARS institutions and the general readiness of NARS institutions to respond to ASWAp research needs.